Crystalline-Like Keratopathy after Intravenous Immunoglobulin Therapy with Incomplete Kawasaki Disease: Case Report and Literature Review - Elif Erdem; Emine Kocabas; Hande Taylan Sekeroglu; Özlem Özgür; Meltem Yagmur; T. Reha Ersoz (Case Reports in Ophthalmological Medicine)
A 7-year-old girl had presented with high body temperature and joint pain which continued for 3 days. Because of the prolonged history of unexplained fever, rash, bilateral nonpurulent conjunctival injection, oropharyngeal erythema, strawberry tongue, and extreme of age, incomplete Kawasaki disease was considered and started on an intravenous immunoglobulin infusion. Six days after this treatment, patient was referred to eye clinic with decreased vision and photophobia. Visual acuity was reduced to 20/40 in both eyes. Slit-lamp examination revealed bilateral diffuse corneal punctate epitheliopathy and anterior stromal haze. Corneal epitheliopathy seemed like crystal deposits. One day after presentation, mild anterior uveitis was added to clinical picture. All ocular findings disappeared in one week with topical steroid and unpreserved artificial tear drops. We present a case who was diagnosed as incomplete Kawasaki disease along with bilateral diffuse crystalline-like keratopathy. We supposed that unusual ocular presentation may be associated with intravenous immunoglobulin treatment.